The Fecal Microbiota of Dogs Switching to a Raw Diet Only Partially Converges to That of Wolves - Xu, Jia; Becker, Anne A. M. J.; Luo, Yu; Zhang, Wenfu; Ge, Bingqian; Leng, Chunqing; Wang, Guyue; Ding, Limin; Wang, Jianmei; Fu, Xiaoyu; Janssens, Geert P. J. (Frontiers in Microbiology, 2021)
The genomic signature of dog domestication reveals adaptation to a starch-rich diet compared with their ancestor wolves. Diet is a key element to shape gut microbial populations in a direct way as well as through coevolution with the host. We investigated the dynamics in the gut microbiota of dogs when shifting from a starch-rich, processed kibble diet to a nature-like raw meat diet, using wolves as a wild reference. Six healthy wolves from a local zoo and six healthy American Staffordshire Terriers were included. Dogs were fed the same commercial kibble diet for at least 3 months before sampling at day 0 (DC), and then switched to a raw meat diet (the same diet as the wolves) for 28 days. Samples from the dogs were collected at day 1 (DR1), week 1 (DR7), 2 (DR14), 3 (DR21), and 4 (DR28). The data showed that the microbial population of dogs switched from kibble diet to raw diet shifts the gut microbiota closer to that of wolves, yet still showing distinct differences. At phylum level, raw meat consumption increased the relative abundance of Fusobacteria and Bacteroidetes at DR1, DR7, DR14, and DR21 (q < 0.05) compared with DC, whereas no differences in these two phyla were observed between DC and DR28. At genus level, Faecalibacterium, Catenibacterium, Allisonella, and Megamonas were significantly lower in dogs consuming the raw diet from the first week onward and in wolves compared with dogs on the kibble diet. Linear discriminant analysis effect size (LEfSe) showed a higher abundance of Stenotrophomonas, Faecalibacterium, Megamonas, and Lactobacillus in dogs fed kibble diet compared with dogs fed raw diet for 28 days and wolves. In addition, wolves had greater unidentified Lachnospiraceae compared with dogs irrespective of the diets. These results suggested that carbohydrate-fermenting bacteria give way to protein fermenters when the diet is shifted from kibble to raw diet. In conclusion, some microbial phyla, families, and genera in dogs showed only temporary change upon dietary shift, whereas some microbial groups moved toward the microbial profile of wolves. These findings open the discussion on the extent of coevolution of the core microbiota of dogs throughout domestication.